3D parametric modeling prototype internal combustion engine means Delcam of PowerSHAPE - Носов, Павло Сергійович (Eastern-European Journal of Enterprise Technologies, 2013)
The features of using computer-aided design systems and modern technologies in the automobile industry are considered in the paper. Methods of using modern information technologies and systems for modeling the structure of internal combustion engines are proposed. The advantages of combining CAD and CAM systems in particular software products are emphasized. Approaches to using Delcam plc products are justified, the sequence of design for ensuring an optimum design solution is specified. The requirements and risk analysis for designing internal combustion engines are given. Special attention was paid to the problem of geometric calculations of the crank mechanism parts when modeling cranks and pistons. An algorithm for constructing the 3D- model of internal combustion engine prototype with increased capacity, without changing the body size, is considered. Design algorithm consists of four stages, each of them determines the final shape of all construction parts.